Communication: Essential Element at International Centers - Francis C. Byrnes (Journal of Applied Communications, 1980)
The first international agricultural research center began operations less than 20 years ago. Not even the most optimistic and enthusiastic supporter of the International Rice Research Institute (IRRI), the first center, would have dared to dream, let alone predict, either its dramatic success or the consequences for peoples and other commodities around the world.